Estudio del protocolo reproductivo en la “Fundación ONCE del Perro Guía (FOPG)” - Carmona Rupérez, Rebeca; Ortega Martín, Cristina (Revista Complutense de Ciencias Veterinarias, 2009)
The Guide Dog ONCE Foundation is appointed to offer guide dogs to blind people. The most important thing is to control the reproductive cycle of males and females in order to obtain the bigger sum of able animals to work. The control is based, in the female, in the detection of estrous, covering or artificial insemination, pregnancy test and control of this and the birth. In case of the male, it´s essentially a quality sperm control. Also, the Foundation is developing a new freezing semen program to preserve the best.